2015
DOI: 10.1093/brain/awv089
|View full text |Cite
|
Sign up to set email alerts
|

The ependymal region of the adult human spinal cord differs from other species and shows ependymoma-like features

Abstract: Several laboratories have described the existence of undifferentiated precursor cells that may act like stem cells in the ependyma of the rodent spinal cord. However, there are reports showing that this region is occluded and disassembled in humans after the second decade of life, although this has been largely ignored or interpreted as a post-mortem artefact. To gain insight into the patency, actual structure, and molecular properties of the adult human spinal cord ependymal region, we followed three approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 69 publications
3
60
1
Order By: Relevance
“…We noted that previous studies based their conclusions that ependymal cells give rise to the majority of scar-forming astrocytes in SCI lesions on the assertion that the majority of those putative astrocytes were “Sox9 positive, vimentin positive and GFAP negative”222324. However, both Sox93637 and vimentin323839 are highly expressed by ependymal cells, raising questions as to the validity of using these markers in the absence of GFAP to identify ependymal progeny as astrocytes. In addition, there is no precedent in the literature for the existence of scar-forming reactive astrocytes that do not express GFAP.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…We noted that previous studies based their conclusions that ependymal cells give rise to the majority of scar-forming astrocytes in SCI lesions on the assertion that the majority of those putative astrocytes were “Sox9 positive, vimentin positive and GFAP negative”222324. However, both Sox93637 and vimentin323839 are highly expressed by ependymal cells, raising questions as to the validity of using these markers in the absence of GFAP to identify ependymal progeny as astrocytes. In addition, there is no precedent in the literature for the existence of scar-forming reactive astrocytes that do not express GFAP.…”
Section: Resultsmentioning
confidence: 93%
“…To identify ependyma we used CD1333132 and vimentin3839, while reactive astrocytes were identified by both GFAP and Aldh1l1 labeling. GFAP was first isolated from CNS lesions40 and has over many decades of research become the canonical maker of astrocyte reactivity in response to CNS damage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Garcia-Ovejero, et al [41] were able to demonstrate that the adult human central canal displays at least three common characteristics distinct from other species: first, a gliosis formed by a dense mesh of glial fibrillary acidic protein-positive ( GFAP+) astrocytic processes. A second feature is the presence of protoplasmic cells or ependymocytes, which show expression of CD15 and glutamate aspartate transporter (GLAST) (now known as SLC1A3), that, in addition to astrocytes, have been related to radial glia and stem/precursor cell phenotypes [41]. Additionally, Paniagua-Torija, et al observed that the ependymal region is enriched in cannabinoid receptor type 1 (CB1), which is involved in the regulation of the neural stem [42].…”
Section: Reviewmentioning
confidence: 99%
“…Additionally, Paniagua-Torija, et al observed that the ependymal region is enriched in cannabinoid receptor type 1 (CB1), which is involved in the regulation of the neural stem [42]. A third feature is the existence of structures previously described as pseudo-canals consisting of cells expressing vimentin and radially oriented around a presumed lumen, which later was discovered to be a blood vessel [41]. Garcia-Ovejero, et al stated that this finding showed the presence of perivascular pseudorosettes, a crucial diagnostic feature for low-grade ependymoma [41-42].…”
Section: Reviewmentioning
confidence: 99%